BEYOND THE CLINIC: A NARRATIVE REVIEW OF DIGITAL BIOMARKERS FOR MONITORING PSYCHOTIC DISORDERS IN NATURALISTIC SETTINGS - Marta Cieślak,; Anna Baranowska,; Aleksandra Oparcik,; Anastazja Orłowa,; Laura Kurczoba,; Anita Pakuła,; Klaudia Martyna Patrzykąt,; Julia Pawłowska,; Kinga Szyszka,; Kamil Turlej, (International Journal of Innovative Technologies in Social Science, 2025)
Psychotic disorders remain a major challenge in psychiatry due to their chronicity and symptom heterogeneity. Digital phenotyping - the passive accumulation of behavioural data via various sensors - offers a pivotal shift toward ecologically valid, continuous monitoring that episodic clinical interviews cannot capture. This review aims to synthesise current literature on digital biomarkers, evaluating their role in predicting disease trajectories and social functioning while addressing inherent methodological and socio-ethical challenges. To achieve this, a comprehensive search of major databases, including PubMed, Scopus, and IEEE Xplore, was conducted to analyse key technological applications and clinical outcomes. We found that smartphones and medical-grade accelerometers remain the predominant tools for data collection, with GPS and mobility metrics serving as main proxies for monitoring symptoms. Simultaneously, next-generation technologies - such as AI-driven home EEG for sleep profiling, AI-driven audiovisual processing of patients’ affect and Natural Language Processing - are redefining the boundaries of what can be captured in the patient's daily environment. However, for these technologies to move beyond research pilots, future frameworks must address current methodological fragmentation through standardised reporting protocols. Ultimately, successful clinical implementation requires an evolution of consent models, ensuring that algorithmic precision is deployed within a user-centred architecture that prioritises patient autonomy and the therapeutic relationship.